A method for strengthening fine-grained cassiterite flotation recovery by using copper-iron-zinc transition metal ion-sodium silicate complex modifier
Patent Information
- Application Number
- CN202611513281.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明提出了一种铜-铁-锌过渡金属离子-水玻璃复配调整剂强化微细粒锡石浮选回收的方法,以解决单一水玻璃调整效果有限、捕收剂利用效率不足和锡回收率偏低的问题
(1)本发明将铜盐、铁盐和锌盐与水玻璃复配,形成铜-铁-锌过渡金属离子-硅酸盐协同调整体系,兼具矿泥分散和锡石活化作用,可改善矿浆分散状态并提高微细粒锡石表面活性,从而提升捕收剂作用效率。
Smart Images

Figure CN122999385A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of mineral processing engineering flotation technology, and particularly relates to a method for enhancing the flotation and recovery of fine-grained cassiterite using a copper-iron-zinc transition metal ion-water glass composite modifier. Background Technology
[0002] Tin is an important non-ferrous metal and strategic mineral resource, and cassiterite is the most important usable mineral among tin resources. As easily beneficiated high-grade tin resources gradually decrease, the proportion of fine-grained cassiterite in actual production is constantly increasing. Fine-grained cassiterite has a small particle size, large specific surface area, and high surface energy. During flotation, it is easily affected by factors such as slime covering, gangue entrainment, and poor pulp dispersion, leading to a reduced probability of particle-bubble collision and adhesion, a slower flotation rate, and a poorer collector effect, resulting in a lower tin recovery rate.
[0003] Currently, cassiterite flotation typically employs hydroxamic acids, fatty acids, or a combination of collectors for recovery, and utilizes silicate modifiers such as water glass to improve pulp dispersion and gangue inhibition. Water glass can form silicate, polymeric silicate, or colloidal silicate components in the pulp, which adsorb onto the surface of slime or gangue minerals, enhancing electrostatic repulsion and hydration between particles, thereby reducing the covering and heterogeneous aggregation of fine slime particles on the cassiterite surface to some extent. However, when water glass is used alone, its regulatory effect on the active sites on the surface of fine cassiterite particles is relatively limited, and there is still room for improvement in simultaneously addressing slime covering and insufficient cassiterite collection efficiency.
[0004] Existing patent documents CN202311350630.7 disclose the application of hydroxamic acid-modified starch-metal ion flocculant in cassiterite flotation, and CN202610478793.0 discloses a slime dispersant and flotation method for lepidolite flotation. These documents respectively relate to cassiterite flotation reagents and lepidolite flotation dispersants; however, no reports have been found in the prior art regarding compound modifiers that combine slime dispersion and cassiterite activation functions for fine-grained cassiterite. Summary of the Invention
[0005] This invention proposes a method for enhancing the flotation recovery of fine-grained cassiterite using a copper-iron-zinc transition metal ion-water glass composite modifier, in order to solve the problems of limited modifier effect of water glass alone, insufficient collector utilization efficiency, and low tin recovery rate.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for enhancing the flotation recovery of fine-grained cassiterite using a copper-iron-zinc transition metal ion-water glass composite modifier includes the following steps: Take cassiterite slurry, add copper-iron-zinc transition metal ions-water glass compound modifier and stir, then add collector and auxiliary collector in sequence, stir and carry out roughing operation to obtain roughing concentrate and roughing tailings; The obtained rough concentrate is then treated again with a collector to obtain tin concentrate. Collectors and auxiliary collectors are added again to the roughing tailings for scavenging to obtain scavenging concentrate and final tailings. The scavenging concentrate is returned to the previous flotation operation.
[0007] The transition metal ions selected in this invention possess characteristics such as tunable valence state, strong coordination ability, and high interfacial reactivity. They can complex or bridge with hydroxyl groups, oxygen sites, and collector coordinating groups on the mineral surface, forming interfacial active sites on the cassiterite surface that are conducive to collector adsorption. When copper, iron, zinc, and other transition metal ions are combined with water glass, they can also form metal-silicate composite structures with silicate components, thereby synergistically regulating the slurry's electrical properties, dispersion state, and cassiterite surface activity, providing a possibility for improving the flotation recovery of fine-grained, difficult-to-float cassiterite.
[0008] Furthermore, in the copper-iron-zinc transition metal ion-water glass compound modifier, the mass ratio of copper-iron-zinc transition metal ions to water glass is 3:7.
[0009] Furthermore, in the copper-iron-zinc transition metal ions, the mass ratio of copper salt, iron salt, and zinc salt is 1:1:1; and the modulus of the water glass is 1.0~4.0.
[0010] Furthermore, the copper salt is selected from one or more of copper sulfate, copper chloride, and copper nitrate.
[0011] Furthermore, the iron salt is selected from one or more of ferric chloride, ferric sulfate, and ferric nitrate.
[0012] Furthermore, the zinc salt is selected from one or more of zinc sulfate, zinc chloride, and zinc nitrate.
[0013] Furthermore, the collector is a hydroxamic acid collector; the auxiliary collector is SN-F.
[0014] Furthermore, during the roughing process, the dosage of the copper-iron-zinc transition metal ion-water glass compound modifier is 50 g / t, the dosage of the collector is 480 g / t, the dosage of the auxiliary collector is 165 g / t, and the roughing operation time is 5 min 30 s.
[0015] Furthermore, during the selection process, the amount of collector added is 50g / t, and the selection time is 8min.
[0016] Furthermore, the scanning and selection operation includes scanning and selection operation I, scanning and selection operation II, and scanning and selection operation III.
[0017] Furthermore, during the scavenging process I, the dosage of the collector is 130 g / t, the dosage of the auxiliary collector is 73 g / t, and the scavenging process I lasts for 3 min 30 s. During the scavenging II operation, the dosage of the collector is 50 g / t, the dosage of the auxiliary collector is 32 g / t, and the scavenging II operation time is 3 min. During the scavenging operation III, the dosage of the collector is 20 g / t, the dosage of the auxiliary collector is 10 g / t, and the scavenging operation III time is 3 min.
[0018] Furthermore, during all operations, each time a new ingredient is added, it needs to be stirred for 3 minutes.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects: (1) The present invention combines copper salt, iron salt and zinc salt with water glass to form a copper-iron-zinc transition metal ion-silicate synergistic adjustment system, which has both the effects of slurry dispersion and cassiterite activation. It can improve the dispersion state of slurry and increase the surface activity of fine cassiterite particles, thereby improving the efficiency of the collector.
[0020] (2) The present invention limits the modulus of water glass and improves the effect of compound modifier by adjusting the polymerization morphology of silicate; under the condition of modulus 3.0, the compound modifier has a better strengthening effect on the flotation recovery of fine cassiterite.
[0021] (3) The present invention is used in conjunction with hydroxamic acid collectors and phosphoric acid auxiliary collectors. The reagent formulation is simple, suitable for fine cassiterite slurry in the field, and is beneficial for industrial application.
[0022] (4) Under the modulus 3.0 condition, the present invention achieved the following flotation indicators: the rougher tin recovery rate increased from 75.78% to 81.20%, the closed-circuit tin recovery rate increased from 78.86% to 85.59%, and the tailings Sn grade decreased from 0.37% to 0.26%, indicating that the compound modifier can effectively enhance the flotation recovery of fine cassiterite. Attached Figure Description
[0023] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a closed-circuit flotation flow chart for the enhanced flotation recovery of fine-grained cassiterite using a copper-iron-zinc transition metal ion-water glass composite modifier according to the present invention. Detailed Implementation
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0026] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0027] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0028] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0029] This invention provides a method for enhancing the flotation recovery of fine-grained cassiterite using a copper-iron-zinc transition metal ion-water glass composite modifier. The method involves taking cassiterite flotation slurry from a mineral processing plant in Yunnan, adding the copper-iron-zinc transition metal ion-water glass composite modifier and stirring, then adding a collector and an auxiliary collector sequentially, stirring, and finally performing flotation to obtain tin concentrate. The specific method includes the following steps: taking cassiterite slurry, adding the copper-iron-zinc transition metal ion-water glass composite modifier and stirring, then adding a collector and an auxiliary collector sequentially, stirring, and performing roughing operations to obtain roughing concentrate and roughing tailings; adding a collector again to the obtained roughing concentrate for cleaning operations to obtain tin concentrate; adding a collector and an auxiliary collector again to the obtained roughing tailings for scavenging operations to obtain scavenging concentrate and final tailings, with the scavenging concentrate returned to the previous flotation stage.
[0030] The mechanism of this invention: Copper, iron, and zinc ions, when combined with water glass, can form metal hydroxyl complexes, metal-silicate composites, or charged silicate polymers, thereby regulating the chemical environment of the slurry solution and the surface charge of the minerals. Copper, iron, and zinc ions can coordinate or complex with water, hydroxyl groups, silicate groups, and collector coordinating groups, constructing interfacial active sites on the cassiterite surface that are conducive to collector adsorption; water glass improves the dispersion of fine-grained slime and inhibits some of the gangue effects. By controlling the modulus of water glass and the ratio of copper, iron, and zinc ions, synergistic control of the cassiterite flotation system can be achieved.
[0031] In the following preferred embodiments of the present invention, the mass fraction ratio of copper-iron-zinc transition metal ions to water glass in the copper-iron-zinc transition metal ion-water glass compound modifier is 3:7, that is, the mass fraction of copper-iron-zinc transition metal ions in the modifier is 30%, and the mass fraction of water glass is 70%. This modifier is added to the fine-grained cassiterite slurry collected on-site. Without further adjusting the slurry pH, a collector and an SN-F auxiliary collector are added sequentially for flotation. This method combines the effects of slime dispersion and cassiterite activation, improving the slurry dispersion state and the surface activity of fine-grained cassiterite, and increasing the collector's efficiency. The reagent formulation of the present invention is simple and suitable for the enhanced recovery of fine-grained cassiterite.
[0032] In the following preferred embodiments of the present invention, the mass ratio of copper salt, iron salt and zinc salt in the copper-iron-zinc transition metal ion is 1:1:1.
[0033] In the following optional embodiments of the present invention, the modulus of the water glass is 1.0 to 4.0, preferably 2.0 to 4.0, and more preferably 3.0.
[0034] In the following optional embodiments of the present invention, the copper salt is selected from one or more of copper sulfate, copper chloride and copper nitrate, preferably copper sulfate.
[0035] In the following optional embodiments of the present invention, the iron salt is selected from one or more of ferric chloride, ferric sulfate and ferric nitrate, preferably ferric chloride.
[0036] In the following optional embodiments of the present invention, the zinc salt is selected from one or more of zinc sulfate, zinc chloride and zinc nitrate, preferably zinc sulfate.
[0037] In the following optional embodiments of the present invention, the collector is a hydroxamic acid collector; the auxiliary collector is SN-F, and SN-F is a phosphate auxiliary collector.
[0038] In the following preferred embodiments of the present invention, during the roughing operation, the dosage of the copper-iron-zinc transition metal ion-water glass composite modifier is 50 g / t, the dosage of the collector is 480 g / t, the dosage of the auxiliary collector is 165 g / t, and the roughing operation time is 5 min 30 s.
[0039] In the following preferred embodiments of the present invention, during the selection process, the amount of collector added is 50 g / t, and the selection time is 8 min.
[0040] In the following preferred embodiments of the present invention, the scanning operation includes scanning operation I, scanning operation II, and scanning operation III, specifically: During the scavenging operation I, the dosage of the collector was 130 g / t, the dosage of the auxiliary collector was 73 g / t, and the operation time of scavenging operation I was 3 min 30 s; During the scavenging II operation, the dosage of the collector is 50 g / t, the dosage of the auxiliary collector is 32 g / t, and the operation time is 3 min. During the scavenging operation III, the dosage of the collector is 20 g / t, the dosage of the auxiliary collector is 10 g / t, and the operation time of scavenging operation III is 3 min.
[0041] In the following preferred embodiments of the present invention, in all operations, stirring is required for 3 minutes after each addition of a raw material.
[0042] In the following preferred embodiments of the present invention, the cassiterite slurry is a fine-grained cassiterite flotation slurry taken from a concentrator in Yunnan Province, with a Sn grade of 1.25~1.30% based on the dry ore of the slurry, and a -20μm particle size ratio of 60~75%; preferably, the -20μm particle size ratio is 65~70%.
[0043] Unless otherwise specified, "room temperature" in this invention refers to 25±2℃.
[0044] All raw materials used in this invention were purchased from the market.
[0045] The technical solution of the present invention will be further illustrated by the following embodiments.
[0046] In the following preferred embodiments of the present invention, the cassiterite slurry is a fine-grained cassiterite flotation slurry received from a concentrator in Yunnan Province. Due to fluctuations in the feed properties and production conditions, the Sn grade and particle size distribution of different batches of slurry vary. Based on dry ore, the Sn grade is 1.25-1.30%, and the mass percentage of -20 μm particles is 60-75%, preferably 65-70%. The above numerical ranges represent typical fluctuations in the actual slurry processed by the present invention. The specific Sn grade of the slurry used in each embodiment is subject to the corresponding experimental results.
[0047] The cassiterite slurry used in the examples was taken from a fine-grained cassiterite flotation slurry collected on-site from a concentrator in Yunnan Province. The properties of the slurry varied slightly from batch to batch, and the reagent dosages were based on the dry weight of the slurry. The compound modifier consisted of water glass, copper salt, iron salt, and zinc salt; the copper salt was copper sulfate, the iron salt was ferric chloride, and the zinc salt was zinc sulfate. The collector and SN-F were both flotation reagents used on-site at the concentrator, with SN-F being a phosphate-based auxiliary collector.
[0048] Example 1 A copper-iron-zinc transition metal ion-water glass composite modifier is used to enhance the roughing process of fine-grained cassiterite. The steps are as follows: (1) Pulp preparation Fine-grained cassiterite flotation slurry was collected from a mineral processing plant in Yunnan Province as the slurry to be processed. (2) Preparation of compound modifiers Copper sulfate, ferric chloride, and zinc sulfate were weighed out in a mass ratio of 1:1:1 and dissolved in water separately. The three metal salt solutions were then mixed thoroughly. Water glass was added in a mass ratio of copper-iron-zinc transition metal ions to water glass of 3:7 and stirred thoroughly to prepare a copper-iron-zinc transition metal ion-water glass composite modifier. The moduli of the water glass were 1.0, 2.0, 3.0, and 4.0, respectively. (3) Coarse selection operation Add 50g / t of the copper-iron-zinc transition metal ion-water glass compound modifier obtained in step (2) to the cassiterite slurry obtained in step (1), and stir for 3 min; then add 480g / t of hydroxamic acid collector, and stir for 3 min; then add 165g / t of SN-F auxiliary collector, and stir for 3 min; then carry out roughing operation for 5 min 30 s to obtain roughing concentrate and roughing tailings; The flotation parameters after balancing are shown in Table 1.
[0049] Table 1. Effects of different moduli of water glass-copper-iron-zinc transition metal ion composite modifiers on cassiterite roughing parameters As shown in Table 1, as the modulus of water glass increases from 1.0 to 3.0, the Sn recovery rate of tin concentrate increases from 78.32% to 81.20%, while the Sn grade of tailings decreases from 0.40% to 0.35%. When the modulus continues to increase to 4.0, the tin recovery rate decreases slightly, indicating that the roughing index of cassiterite is better under the modulus of 3.0.
[0050] Example 2: Closed-circuit flotation test under the condition of copper-iron-zinc transition metal ions and water glass with a modulus of 3.0. A method for enhancing the flotation recovery of fine-grained cassiterite using a copper-iron-zinc transition metal ion-water glass composite modifier, comprising the following steps: (1) Pulp preparation Fine-grained cassiterite flotation slurry was collected from a mineral processing plant in Yunnan Province as the slurry to be processed. (2) Preparation of compound modifiers Copper sulfate, ferric chloride, and zinc sulfate were compounded with water glass to prepare a copper-iron-zinc transition metal ion-water glass compound modifier, wherein the mass ratio of copper sulfate, ferric chloride, and zinc sulfate was 1:1:1; the mass fraction ratio of copper-iron-zinc transition metal ions to water glass was 3:7; and the modulus of the water glass was 3.0. (3) Coarse selection operation use Figure 1 The closed-loop process is as follows: 50 g / t of copper-iron-zinc transition metal ion-water glass compound modifier obtained in step (2) is added to the cassiterite slurry obtained in step (1), and stirred for 3 min; then 480 g / t of hydroxamic acid collector is added, and stirred for 3 min; then 165 g / t of SN-F auxiliary collector is added, and stirred for 3 min; then roughing operation is carried out, and the roughing operation time is 5 min 30 s, to obtain roughing concentrate and roughing tailings; (4) Selected assignments Add 50 g / t of hydroxamic acid collector to the rough concentrate obtained in step (3), stir for 3 min and then carry out the cleaning operation for 8 min to obtain tin concentrate; (5) Sweeping and sorting operations Add 130g / t of hydroxamic acid collector and 73g / t of SN-F auxiliary collector to the rough tailings obtained in step (3) in sequence, stir for 3 minutes and then carry out scavenging operation I. The scavenging operation I time is 3 minutes and 30 seconds. Continue adding 50 g / t of hydroxamic acid collector and 32 g / t of SN-F auxiliary collector, stir for 3 min and then carry out scavenging operation II for 3 min; Continue adding 20 g / t of hydroxamic acid collector and 10 g / t of SN-F auxiliary collector, stir for 3 min and then carry out scavenging operation III for 3 min; (6) Products After the roughing, cleaning, and scavenging processes described above, tin concentrate was obtained. The flotation parameters after equilibrium are shown in Table 2.
[0051] Table 2. Closed-circuit flotation test results of copper-iron-zinc transition metal ions under the condition of water glass compound modulus 3.0. Comparative Example 1: Closed-circuit flotation test under no modifier conditions Same as Example 2, except that no copper-iron-zinc transition metal ion-water glass composite modifier is added. The flotation parameters after equilibrium are shown in Table 3.
[0052] Table 3 Results of closed-circuit flotation tests under no modifier conditions As shown in Tables 3 and 2, after adding the copper-iron-zinc transition metal ion-modulus 3.0 water glass compound modifier, the closed-circuit tin recovery rate increased from 78.86% to 85.59%, an increase of about 6.7 percentage points, and the Sn grade of tailings decreased from 0.37% to 0.26%.
[0053] Comparative Example 2: Rough Separation Test of Cassiterite under the Conditions of Copper-Iron-Zinc Transition Metal Ions-Water Glass Compound Modifier with Modulus 3.0 Similar to Example 2, except that only coarse flotation is performed, without fine flotation or sweeping flotation. The flotation parameters are shown in Table 4.
[0054] Table 4. Results of rough selection test of cassiterite under the condition of copper-iron-zinc transition metal ions-modulus 3.0 water glass compound modulator. Comparative Example 3: Cassiterite coarse selection test under no modifier conditions Similar to Example 2, except that no copper-iron-zinc transition metal ion-water glass composite modifier is added, and only roughing is performed, without cleaning or scavenging operations. Flotation parameters are shown in Table 5.
[0055] Table 5 Results of cassiterite coarse separation test under no modifier conditions As shown in Tables 5 and 4, after adding the copper-iron-zinc transition metal ion-modulus 3.0 water glass compound modulator, the Sn grade of tin concentrate increased from 3.38% to 3.54%, and the Sn recovery rate increased from 75.78% to 81.20%, an increase of about 5.4 percentage points.
[0056] Comparative Example 4: Rough Selection Test of Iron-Deficient Salts Similar to Example 1, except that the compound modifier is composed of copper sulfate, zinc sulfate, and water glass, with a copper sulfate to zinc sulfate mass ratio of 1:1, and the total mass ratio of copper and zinc transition metal ions to water glass remains 3:7. Except for the above variables, the reagent formulation and roughing conditions are the same as in Example 1, and the experimental results are shown in Table 6.
[0057] Table 6 Results of roughing tests on cassiterite under iron-deficient salt conditions As shown in Table 6, the recovery rate of tin concentrate Sn was 79.24% after the absence of iron salts, which was lower than 81.20% under the modulus 3.0 condition in Example 1. This indicates that the synergistic combination of copper, iron and zinc metal salts is beneficial to the flotation recovery of cassiterite.
[0058] Comparative Example 5: Adding a metal salt roughing test Similar to Example 1, except that manganese sulfate was added to the ingredients copper sulfate, ferric chloride, and zinc sulfate, with the mass ratio of the four metal salts being 1:1:1:1. The total mass ratio of copper, iron, zinc, and manganese transition metal ions to water glass remained 3:7. Apart from the above variables, the reagent formulation and roughing conditions were the same as in Example 1. The experimental results are shown in Table 7.
[0059] Table 7 Results of roughing tests on cassiterite under conditions with added metal salts As shown in Table 7, the Sn recovery rate of tin concentrate after adding manganese sulfate was 80.10%, which did not exceed 81.20% in Example 1, indicating that adding metal salts did not further improve the roughing recovery effect of cassiterite.
[0060] Comparative Example 6: Rough Selection Test of Metal Salt Proportioning Same as Example 1, except that the mass ratio of copper sulfate, ferric chloride, and zinc sulfate was adjusted to 2:1:1, and the total mass ratio of copper, iron, and zinc transition metal ions to water glass remained at 3:7. Apart from the above variables, the reagent formulation and roughing conditions were the same as in Example 1. The experimental results are shown in Table 8.
[0061] Table 8 Results of roughing tests on cassiterite under different metal salt ratios As shown in Table 8, when the mass ratio of copper sulfate, ferric chloride and zinc sulfate was adjusted to 2:1:1, the recovery rate of tin concentrate Sn dropped to 79.79%, indicating that the ratio of the three metal salts affects the effect of the compound modifier.
[0062] Comparative Example 7: Rough Selection Test of Metal Salt / Water Glass Ratio Same as Example 1, except that the mass ratio of the total mass of copper, iron, and zinc transition metal ions to the mass of water glass was adjusted from 3:7 to 5:5, while the mass ratio of copper sulfate, ferric chloride, and zinc sulfate remained 1:1:1. Apart from the above variables, the reagent formulation and roughing conditions were the same as in Example 1, and the experimental results are shown in Table 9.
[0063] Table 9. Results of roughing tests on cassiterite under different metal salt / water glass ratios. As shown in Table 9, when the total mass ratio of copper, iron, and zinc transition metal ions to water glass was adjusted to 5:5, the recovery rate of tin concentrate Sn dropped to 79.12%, indicating that the ratio of transition metal ions to water glass has an impact on the effect of the compound modifier.
[0064] Comparative Example 8: Rough Selection Test of Anhydrous Glass Similar to Example 1, except that water glass was not added to the compound modifier; only copper sulfate, ferric chloride, and zinc sulfate were added, with the mass ratio of copper sulfate, ferric chloride, and zinc sulfate remaining at 1:1:1. Apart from the above variables, the reagent formulation and roughing conditions were the same as in Example 1, and the experimental results are shown in Table 10.
[0065] Table 10 Results of roughing tests on cassiterite under anhydrous glass conditions As shown in Table 10, without the addition of water glass, the Sn recovery rate of tin concentrate decreased to 78.25%, which is lower than the 81.20% under the modulus 3.0 condition in Example 1. This indicates that the addition of water glass is beneficial to the copper, iron and zinc transition metal ion complex system in exerting the cassiterite flotation enhancement effect.
[0066] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for enhancing the flotation recovery of fine-grained cassiterite using a copper-iron-zinc transition metal ion-water glass composite modifier, characterized in that, Includes the following steps: Take cassiterite slurry, add copper-iron-zinc transition metal ions-water glass compound modifier and stir, then add collector and auxiliary collector in sequence, stir and carry out roughing operation to obtain roughing concentrate and roughing tailings; The obtained rough concentrate is then treated again with a collector to obtain tin concentrate. Collectors and auxiliary collectors are added again to the roughing tailings for scavenging to obtain scavenging concentrate and final tailings. The scavenging concentrate is returned to the previous flotation operation.
2. The method according to claim 1, characterized in that, In the copper-iron-zinc transition metal ion-water glass compound modifier, the mass ratio of copper-iron-zinc transition metal ions to water glass is 3:
7.
3. The method according to claim 2, characterized in that, In the copper-iron-zinc transition metal ions, the mass ratio of copper salt, iron salt and zinc salt is 1:1:1; The modulus of the water glass is 1.0 to 4.
0.
4. The method according to claim 3, characterized in that, The copper salt is selected from one or more of copper sulfate, copper chloride and copper nitrate; The iron salt is selected from one or more of ferric chloride, ferric sulfate and ferric nitrate; The zinc salt is selected from one or more of zinc sulfate, zinc chloride, and zinc nitrate.
5. The method according to claim 1, characterized in that, The collector is a hydroxamic acid collector; the auxiliary collector is SN-F.
6. The method according to claim 1, characterized in that, During the roughing process, the dosage of the copper-iron-zinc transition metal ion-water glass compound modifier is 50 g / t, the dosage of the collector is 480 g / t, the dosage of the auxiliary collector is 165 g / t, and the roughing operation time is 5 min 30 s.
7. The method according to claim 1, characterized in that, During the selective cleaning process, the amount of collector added is 50g / t, and the selective cleaning time is 8min.
8. The method according to claim 1, characterized in that, The scanning and selection operation includes scanning and selection operation I, scanning and selection operation II, and scanning and selection operation III.
9. The method according to claim 8, characterized in that, During the scavenging process I, the dosage of the collector is 130 g / t, the dosage of the auxiliary collector is 73 g / t, and the scavenging process I lasts for 3 min 30 s. During the scavenging II operation, the dosage of the collector is 50 g / t, the dosage of the auxiliary collector is 32 g / t, and the scavenging II operation time is 3 min. During the scavenging operation III, the dosage of the collector is 20 g / t, the dosage of the auxiliary collector is 10 g / t, and the scavenging operation III time is 3 min.
10. The method according to claim 1, characterized in that, During all operations, each time a new ingredient is added, it needs to be stirred for 3 minutes.
Citation Information
Patent Citations
Application of hydroxamic acid modified starch-metal ion flocculant in cassiterite flotation
CN117324132B
Slurry dispersing agent for lepidolite ore flotation and flotation method
CN122076617A
